Social stratification and consumption of music in Athens - Σουλιώτης Νίκος; Εμμανουήλ Δημήτρης (The Greek Review of Social Research, 2016)
The paper examines the relation of social stratification with consumption of music in public venues in Athens. Data comes from a questionnaire survey based on a stratified random sample. The analysis focuses, firstly, on the patterns of consumption and, secondly, on the relation of these patterns with the dimensions of social stratification (socio-economic class, status, education, income). We find that «omnivore» music consumers are a rather small group and that the opposition between high and popular culture still structures the pattern of music consumption in Athens, although the limits between these two cultural poles are attenuated. On the other hand, in terms of social structure, the «popular» pattern of consumption has a pronounced inter-class character thus undermining simple models of one-to-one correspondence between social strata and culture. Amongst dimensions of social stratification, education and status have the most determinant role in shaping the consumption patterns, while the influence of socio-economic class appears to be statistically insignificant.